RELAÇÕES ENTRE LIDERANÇA AUTÊNTICA, PERCEPÇÃO DE SUPORTE SOCIAL, RESILIÊNCIA E ENGAJAMENTO NO TRABALHO - MORAES, ELTON RAMOS (2019)
This study aims to investigate the effects of authentic leadership and social support on organisational engagement, moderated by resilience factors. The theoretical underpinning of this investigation is the job demands-resource model, which proposes that high job demands along with limited resources may affect the employee engagement and consequently his or her health and well-being. A total of 298 workers were invited via social media to respond to four separate Likert scales measuring authentic leadership, social support, organisational engagement and resilience. As the instruments were previously validated based on different populations, the first step of data analysis was to investigate the construct validity of each scale. Whereas engagement and authentic leadership are unidimensional constructs, social support is comprised of two dimensions (emotional support and general support) and resilience of three dimensions (acquiescence, spirituality, persistence). Structural equation modelling was used to test the moderation effect of resilience on the relationship between the explanatory variables authentic leadership and social support and the response variable organisational engagement. The results showed that general perception of social support at work was the only variable that have a significant direct effect on employee engagement, with no significant associations being found between engagement, emotional support dimension and authentic leadership. Nevertheless, when each of the three resilience dimensions interact with leadership and social support, they both predict significantly employee engagement. These findings are consistent with the job demands-resource model, which consider resilience as one of the main resources the individuals deploy to cope with difficult job demands. Although a clear perception about the leader's legitimacy and an effective social support in the workplace are important variables for the prediction of employee engagement, the influence of external characteristics should not be considered independently of internal factors, such as resilience, when employee engagement is investigated.